Analysis of the Influence of Competence, Work Motivation and Work Culture on Personnel Performance in the KU (Finance) Environment of the TNI, Central Java Region, Pusku TNI - Oktarina Prananingrum, Enggar; Khaeruddin (Dinasti International Journal of Digital Business Management, 2025)
This research aims to analyze the influence of competence, work motivation and organizational culture on personnel performance in the financial environment of the Indonesian National Army (TNI) Central Java Region. In military organizations, especially in the financial sector, aspects of individual competence, motivational drive, and organizational cultural values ??play an important role in work effectiveness and transparent and accountable budget management. The research method used is qualitative with a phenomenological study approach. Data was collected through in-depth interviews, participant observation and document analysis, involving financial personnel within the TNI as key informants. The research results show that high competence, both in technical and managerial aspects, contributes to improving individual performance. In addition, work motivation, whether originating from intrinsic or extrinsic factors, is the main driving factor in maintaining the effectiveness and efficiency of financial management. Meanwhile, a strong organizational culture—including the values ??of discipline, loyalty, and integrity—has a significant impact in creating a professional and responsible work environment. The implications of this research indicate that increasing personnel competency through continuous training, providing appropriate incentives to increase motivation, and strengthening organizational culture based on TNI values ??can be the main strategy in improving the quality of financial management. Thus, it is hoped that the results of this research will provide insight for TNI leaders in formulating more effective and efficient human resource management policies.